Zinc, copper and iron concentrations in cerebral cortex of male rats exposed to formaldehyde inhalation - Özen, OA; Songur, A; Sarsilmaz, M; Yaman, M; Kus, I (Elsevier Gmbh, 2003)
Retrospective cohort studies and clinical findings have suggested effects of formaldehyde exposure on the central nervous system in anatomists, embalmers and pathologists. On the other hand, harmful effects of formaldehyde inhalation on the nervous system are not well documented. The concentrations of elements such as zinc, copper and iron within the cerebral cortex indicate whether physiological conditions are maintained. In this study, adult mate albino Wistar rats were exposed to formaldehyde at different concentrations (0; 6.1; 12.2 mg . m(-3)) and during different periods of time (subacute-subchronic), and body weights were recorded weekly. Zinc, copper and iron concentrations were measured in the parietal cortex using atomic absorption spectrometry after wet ashing. We conclude that subacute or subchronic exposure to formaldehyde may cause growth retardation and alter zinc, copper and iron levels in the cerebral cortex.
Keywords: formaldehyde exposure; inhalation; cerebral cortex; zinc; copper; iron